2021
DOI: 10.1063/5.0036018
|View full text |Cite
|
Sign up to set email alerts
|

Aerodynamic interaction of bristled wing pairs in fling

Abstract: Tiny flying insects of body lengths under 2 mm use the “clap-and-fling” mechanism with bristled wings for lift augmentation and drag reduction at a chord-based Reynolds number (Re) on O(10). We examine the wing–wing interaction of bristled wings in fling at Re = 10 as a function of initial inter-wing spacing (δ) and degree of overlap between rotation and linear translation. A dynamically scaled robotic platform was used to drive physical models of bristled wing pairs with the following kinematics (all angles r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Furthermore, by virtue of the high fluid viscosity and strong viscous diffusion, the boundary layer on the cylinder surface grows thick enough to overlap with the other boundary layer of the adjacent cylinder and forms a virtual fluid barrier in the gap, suppressing the penetration of fluid through the gap. This phenomenon of hydrodynamic blockage occurs between close solid structures in the low-Reynolds-number flow regime, and is a crucial mechanism for the propulsion and passive transport of tiny organisms with clustered appendages (Barta & Weihs 2006;Nawroth et al 2010;Kolomenskiy et al 2020;Lee, Lee & Kim 2020a;Lee et al 2020b;Kasoju & Santhanakrishnan 2021;Lee & Kim 2021). Consistent with the previous studies, it is reasonable to expect that the effect of the fluid barrier in this study is stronger for narrow gaps than for wide gaps.…”
Section: Thrust Generation Mechanism Of Coordinated Motionsupporting
confidence: 90%
See 1 more Smart Citation
“…Furthermore, by virtue of the high fluid viscosity and strong viscous diffusion, the boundary layer on the cylinder surface grows thick enough to overlap with the other boundary layer of the adjacent cylinder and forms a virtual fluid barrier in the gap, suppressing the penetration of fluid through the gap. This phenomenon of hydrodynamic blockage occurs between close solid structures in the low-Reynolds-number flow regime, and is a crucial mechanism for the propulsion and passive transport of tiny organisms with clustered appendages (Barta & Weihs 2006;Nawroth et al 2010;Kolomenskiy et al 2020;Lee, Lee & Kim 2020a;Lee et al 2020b;Kasoju & Santhanakrishnan 2021;Lee & Kim 2021). Consistent with the previous studies, it is reasonable to expect that the effect of the fluid barrier in this study is stronger for narrow gaps than for wide gaps.…”
Section: Thrust Generation Mechanism Of Coordinated Motionsupporting
confidence: 90%
“…2020; Lee, Lee & Kim 2020 a ; Lee et al. 2020 b ; Kasoju & Santhanakrishnan 2021; Lee & Kim 2021). Consistent with the previous studies, it is reasonable to expect that the effect of the fluid barrier in this study is stronger for narrow gaps than for wide gaps.…”
Section: Resultsmentioning
confidence: 99%
“…Two-dimensional numerical simulations of flows past evenly spaced cylinder lattices showed that the throughflow in the gaps reduces the aerodynamic forces 15,16 . Experiments with mechanical comb-like models suggested a somewhat greater lift to drag ratio during the clap-and-fling phase of the wing motion 17,18,19 , but did not cover the full flapping cycle. Meanwhile, with the state-of-the-art high-speed videography, it became clear that the smaller insects use a wing beat cycle different from that of the larger ones 10,11 , but the role of ptiloptery in this cycle was not considered.…”
mentioning
confidence: 99%
“…Experiments indicated that the lift generated by simplified bristled wing models in the "fling" motion at Re = 10 is slightly smaller than that of the corresponding membrane wings, but the drag on the bristled wings is greatly reduced. Therefore, the lift-to-drag ratio of the bristled wings is much greater than that of the membrane wings 15,16 . In addition, pausing before the start of fling has been shown to reduce power required.…”
Section: Openmentioning
confidence: 96%